The Relationship Between Gender and Weight, Height, Age, Pregnancy, Heredity, Joint Laxity, Body Mass Index, and Physical Activity in Spondylolisthesis Patients at RSUP Fatmawati Jakarta in 2023-2024 - Fauzi, Ahmad; Noerhadiono, Donny; Rayman, Rahmatullah (Medula, 2025)
Spondylolisthesis is the displacement of a vertebra relative to the vertebra below it, causing pain. While various risk factors for spondylolisthesis exist, few studies have explored which risk factors are specific to one gender. Therefore, this study aims to find the relationship between gender and parameters that are commonly considered risk factors for spondylolisthesis. This cross-sectional study was conducted from May to June 2024. A total of 35 patients with spondylolisthesis who underwent surgery at RSUP Fatmawati Jakarta were selected. Patient data were collected from medical records and screened based on inclusion and exclusion criteria. Of the patients, 45.7% were male and 54.3% were female. The data were analyzed using SPSS 16.0. There was a significant difference in the average weight and height between male and female spondylolisthesis patients (weight p=0.017<∝, height p=0.000<∝). There was no significant difference in age. Women with multigravida had the highest frequency (19) compared to primigravida (5), indicating a potential risk factor. No differences were found in joint laxity (p=0.968>∝), BMI, heredity (p=0.922>∝), or physical activity (p=0.076>∝) between genders. There are various risk factors for spondylolisthesis. This study found significant differences in weight and height between genders in spondylolisthesis cases, but no significant differences in other parameters. The study also suggests that multiparity may be a significant risk factor, although further research is needed to confirm this